Psychological Reasons of the Occurrence of Modern Adolescents` Self Injecting Behavior - Varava, Liudmyla; Sipailova, Oleksandra (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article is devoted to an urgent problem of modern society – the phenomenon of self-harming behavior among teenagers. Understanding the nature of the emergence of self-damaging behavior acts, the factors that are the catalyst for these actions, is beyond doubt, since awareness of this issue will help the psychologist to identify the target constructs for further practical work. The main aspects of the concept of self-harming behavior, the causes and factors of occurrence were analyzed. The psychological characteristics of adolescence and the crisis of growing up were explained as one of the main factors in the development of self-harming behavior. It was determined that the psychological characteristics of adolescence together with external factors complicate the process of forming adaptive strategies with the environment. Self-injurious behavior is the result of the adolescent’s search for interaction with his own «I», and, as a result, difficulties arise in the formation of a subjective position and adequate ideas about himself. Among teenagers who commit acts of self-damaging behavior, the mechanisms for the occurrence of these actions have been determined, namely, there are observed violations of emotional regulation, as well as high level of internal conflict, which is accompanied by a heightened sense of guilt. Analisis of the questionnaire was based on the results of 3 groups of children were identified: the first – with the up-to-date experience of self-harming behavior, the second – with a penchant to self-harming behavior and the third – not inclined to self-harm. Thus, the distribution will help the psychologist to select the most effectively corrective program and provide psychological assistance with such requests. A comparative analysis was made between the choice of the method of self-harm and the tendency to such behavior. It was determined that somatic acts of self-harm are characteristic all groups of adolescents and are perceived by them as a bad habit. It was found that the leading reasons for committing acts of self-harm for all groups of adolescents is desire to calm dawn, to pull oneself together, to cope with emotions. It was detected that such indicators complicate the formation of adequate ideas of self perception and become a threat in the formation of the subjective position, and have a destructive effect on the planning of teenager`s own life activity.